2023
DOI: 10.1093/bjd/ljad303
|View full text |Cite
|
Sign up to set email alerts
|

Resident cutaneous memory T cells: a clinical review of their role in chronic inflammatory dermatoses and potential as therapeutic targets

James P Pham,
Kirsty J L Wark,
Jane Woods
et al.

Abstract: Resident memory T-cells (T-RMs) remain in epithelial barrier tissues after antigen exposure and the initial effector phase. These T-RMs provide effective antimicrobial and anticancer immunity, however pathogenic T-RMs have been shown to mediate various chronic inflammatory disorders in a variety of tissue types. In the skin, T-RMs are referred to as resident cutaneous memory T-cells (cT-RMs). Understanding the mechanisms leading to the development and establishment of these cT-RMs populations may allow for tar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 95 publications
0
2
0
Order By: Relevance
“…In the skin, T cells play important roles in protective immunity and the development of inflammatory and autoimmune diseases [ 63 , 64 , 65 ]. Several studies have examined the role of 1,25(OH) 2 D and the VDR in T-cell development, differentiation, and function.…”
Section: Effect Of 125(oh) 2 D On Cells In the Skinmentioning
confidence: 99%
“…In the skin, T cells play important roles in protective immunity and the development of inflammatory and autoimmune diseases [ 63 , 64 , 65 ]. Several studies have examined the role of 1,25(OH) 2 D and the VDR in T-cell development, differentiation, and function.…”
Section: Effect Of 125(oh) 2 D On Cells In the Skinmentioning
confidence: 99%
“…Several studies have found the presence of a “molecular scar” in resolved skin, which may be involved in disease relapse [ 16 , 17 ]. Pathogenic tissue-resident memory T-cells (TRMs) have been proposed as key players in disease memory in psoriasis and other chronic skin diseases [ 18 , 19 , 20 ]. TRMs are dependent on interaction with the local microenvironment, and specifically the pluripotent cytokine transforming growth factor beta (TGFbeta), the metabolic factors fatty-acid-binding proteins 4 and 5, and the cytokines IL-7 and IL-15 are involved in the differentiation and maintenance of TRMs [ 21 , 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%